Tradisi Pembacaan Al-Qur’an Surah-Surah Pilihan: : Kajian Living Qur’an terhadap Pengasuh PP. Annuqayah Daerah Lubangsa Guluk-guluk Sumenep - Ahmad Fuad Hikam; Abd. Mun'em (Program Studi Ilmu Al-Qur’an dan Tafsir, Fakultas Ushuluddin, Universitas Annuqayah (UA), 2024)
This research discusses the practices of Annuqayah caregivers in Lubangsa area who reads selected surahs during fardhu prayers using certain surahs which in fact become their unique characteristics. This kind of practice is very urgent to discuss and is intended to help increase public awareness in interacting with the Qur'an. The surahs that are read and become typical readings in the performance of fardhu prayers are divided into five parts. First, the Dhuhur prayers reads surah al-Kāfirūn and al-Ikhlāṣ. Second, the 'Aṣr prayer reads surah al-'Aṣr and al-Ikhlāṣ. Third, the Maghrib prayer reads al-Fatḥ and al-Ikhlāṣ. Fourth, Ishā' prayer reading surah al-Tīn and al-Qadr. Fifth, the morning prayer reads surah al-Inshirāḥ and al- Fīl. Meanwhile, the focus of the discussion in this research is how to reveal the meaning of the tradition of reading selected surahs of the Quran and what the implications are for pesantren students in Annuqayah Lubangsa area? The type of research used in writing this thesis is fieald research which uses descriptive-qualitative methods with a phenomenological approach. This research concludes that reading the Qur'an is the choice of Annuqayah caregivers. Annuqayah in Lubangsa area means an implementation of the traditions of caregivers which is a form of obedience and devotion to their ancestors. Apart from that, this kind of tradtition is carried out as an effort to shape the character of the students in order to practice the worship that is typical of the Annuqayah teachers in Lubangsa area.